2014
DOI: 10.1097/mnm.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neck pain with 18F-NaF PET/CT

Abstract: As our experience with (18)F-NaF PET/CT broadens, we believe that it will become an increasingly important tool in the evaluation and management of the symptomatic cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Other studies have used NaF-PET to investigate the spine, however, this study is novel in its assessment of healthy subjects. Most studies confirmed PET as an appropriate diagnostic modality in qualitatively diagnosing specific disorders in the spine, such as spinous process injuries, localized facet inflammation or spondylolysis [36,37]. Win et al used NaF-PET to correlate tracer uptake in individual vertebrae with age and weight [11].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used NaF-PET to investigate the spine, however, this study is novel in its assessment of healthy subjects. Most studies confirmed PET as an appropriate diagnostic modality in qualitatively diagnosing specific disorders in the spine, such as spinous process injuries, localized facet inflammation or spondylolysis [36,37]. Win et al used NaF-PET to correlate tracer uptake in individual vertebrae with age and weight [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, few other studies examined hypermetabolic facet arthropathy with nuclear or hybrid imaging modalities. While the majority of these studies used SPECT or SPECT/CT with 99 mTc‐labelled phosphate derivatives or PET/CT with 18 F for the identification of hypermetabolic facet arthropathy, 18 F‐FDG has also been proven useful in this indication. For instance, Rosen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In order to account for the weight difference in rats and the [ 18 F] doses of injected FDG, we calculated the standardized uptake value (SUV). The semi-quantitative SUV measurement is the most widely used in [ 18 F] FDG PET studies of both small animals and humans ( Byrnes et al, 2014 ; Deleye et al, 2014 ). The software used was PMOD 3.6 (PMOD Technologies Ltd., Zurich, Switzerland).…”
Section: Methodsmentioning
confidence: 99%